A Comparative Study of Energy Loss in Ogee-Crested and Round-Crested Weirs through Laboratory Testing - Rahmadani Ari Saputra; Totoh Andayono (MASALIQ, 2026)
Crest geometry is a critical determinant of energy transformation in open-channel flow; however, direct laboratory comparisons between ogee-crested and round-crested weirs remain limited. This study aimed to analyze and compare energy loss across both weir types under equivalent experimental conditions. A quantitative laboratory-experimental design was employed using an open-channel flume at the Hydraulics Laboratory, Department of Civil Engineering, Universitas Negeri Padang. Each weir model was tested in three trials, with channel-bed elevation, flow depth, and flow velocity measured at the upstream, crest, and downstream sections. Total energy loss was calculated using Bernoulli’s equation, while frictional loss was estimated using the Darcy–Weisbach equation. The ogee-crested weir produced a mean total energy loss of 14.63 cm, whereas the round-crested weir produced 13.74 cm, yielding a difference of 0.89 cm. Frictional losses were 0.86 cm for the ogee-crested weir and 1.18 cm for the round-crested weir. Reynolds numbers of 33,408 and 40,880, respectively, indicated turbulent flow in both models. These findings demonstrate that total energy loss was governed not only by frictional resistance but also by turbulence and crest geometry. Under the tested conditions, the round-crested weir retained flow energy more effectively than the ogee-crested weir. This study contributes empirical evidence on the hydraulic performance of different crest geometries and provides practical insight for selecting weir configurations in open-channel flow applications.